A Mobile application for reporting aggregate HIV data: case study of HIV clinics in Kajiado Kenya - Maringa, Margaret. (Strathmore University, 2016)
Data collection and reporting is one of the most important components of monitoring and evaluation of public health programs. Changes in HIV infection rates over time have been hard to interpret in many contexts because programs frequently lack complementary information on changes in behaviour. The impacts of prevention programs on behaviour often remain uncertain because behavioural data is not collected or incomplete. Health service providers at county and national level and policy makers need timely reports with accurate data in order to improve the quality of health care services. On the ground, however, collection of HIV data reports has proved difficult due to poor and unevenly developed infrastructure and lack of human resource to facilitate collection and collation of paper-based reports. This often leads to untimely reporting because of the time it takes to deliver reports to the sub-county and county levels. In this study, the researcher looks at the current data reporting tools used in the health facilities as well as other existing health data reporting systems used in other countries. The researcher also through formal interviews and observation in various facilities in Kajiado County Kenya, was able to note the need for a mobile application to enable in the reporting of HIV related data from the health care facilities to the national level for decision making. This study then proposes development of a mobile application using the android platform that will offer ways of reporting HIV data from health facilities through mobile phones to a centralized database. This solution will help reduce the amount of time it takes for sub-counties to get reports from the facilities thus availability of data for analysis and effective decision-making.
Thesis Submitted in partial fulfillment of the requirements for the Degree of Science in Mobile Telecommunication and Innovation (MSc. MTI) at Strathmore University